Guía de los usos sociales, rituales y actos festivos de la comuna de Joseguango alto parroquia Mulaló cantón Latacunga. - Morales Molina, Mayra Gabriela (2020)
The present researching aims to register and capture into a descriptive guide each of the social uses, rituals and festive events found in the commune Joseguango Alto located in Mulaló parish. First, it was carried out the situational diagnosis of the area under study through the collection of primary and secondary sources where was identified that the main economic source is the agricultural active as well as cultural wealth is related to different traditions and customs, which performed an inventory through the registration of the cultural manifestations existing in the commune applying the file card of the NICH Instituto Nacional del Patrimonio Cultural, in which it was found registered 5 festivals among which the following sub-scopes are registered: religious parties or ceremonies, parties or commemorations and other festive celebrations. Within the possibility of parties, we can remark that in the organization and preparations to perform those celebrations the “priostes” mainly finance food hornado with potatoes, peanut souce, chichi de jora and chicken soup. Finally, it was registered chound 7 rituals divided into different sub-scopes such os rits of passage, commemoration and apotropaises. These are characterized because the peoples who organize are independent, that is some families or couplesdo, so all of the before mentioned have a level of sensitivity to low change. Based on this, the descriptive guide has been designed and reflected all the information collected in the inventory, which is composed by the most relevant data in order to be spread. The guide has reference photographs of the uses of social data, rituals and festive events and it is classified according to the registered and researched areas.